Numerical Simulation of Natural Convection in a Square Cavity Utilizing Nanofluid and Subjected to Air Stream Cooling - Saleem, Khalid B. (Basrah Journal for Engineering Sciences, 2018)
This study numerically investigates natural convection of Cu-water nanofluid in a square cavity subjected to a cooling air stream along the left wall, with the right and bottom walls maintained at cold (TC) and hot (TH) temperatures, respectively, while the top wall is adiabatic. The nanofluid flow is assumed laminar and governed by the Boussinesq approximation. The governing equations are solved using the finite volume method in ANSYS FLUENT. Simulations are performed for nanofluid volume fractions (φ = 0–0.16), Rayleigh numbers (Ra = 10³–10⁵), and free stream Reynolds numbers (Re∞ = 10³–10⁴). The effects of these parameters on stream function (ψ), temperature contours (θ), and average Nusselt number (Nuavg) are analyzed. Results indicate that heat transfer rates increase with higher φ, Ra, and Re∞. Increasing φ and Ra enhances circulation within the cavity, whereas higher Re∞ induces secondary vortices and reduces circulation in the primary vortex. Comparisons of local Nusselt numbers and temperature distributions with previous studies show good agreement, with maximum errors of 14.28% and 3.2%, respectively.